2020
DOI: 10.1177/2474126420941372
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Retinotomy vs Perfluorocarbon Liquid to Aid Drainage of Subretinal Fluid During Primary Rhegmatogenous Retinal Detachment Repair (PRO Study Report No. 10)

Abstract: Purpose: This work compares posterior retinotomy vs perfluorocarbon liquid (PFCL) for subretinal fluid (SRF) drainage during pars plana vitrectomy for primary rhegmatogenous retinal detachment (RRD). Methods: In this large, multicenter, retrospective comparative study, 2620 patients underwent pars plana vitrectomy (with or without scleral buckle) for uncomplicated RRD. Patients for whom SRF was drained via the primary break without retinotomy or PFCL were excluded; those who required both retinotomy and PFCL w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…There were no differences in visual acuity, SSSR, or postoperative ERM formation between the two cohorts. The PFCL cohort, though, did have a higher rate of subsequent vitreoretinal surgeries, possibly because of a higher rate of retained subretinal PFCL in this cohort [15].…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…There were no differences in visual acuity, SSSR, or postoperative ERM formation between the two cohorts. The PFCL cohort, though, did have a higher rate of subsequent vitreoretinal surgeries, possibly because of a higher rate of retained subretinal PFCL in this cohort [15].…”
Section: Introductionmentioning
confidence: 69%
“…There were no differences in visual acuity, SSSR, or postoperative ERM formation between the two cohorts. The PFCL cohort, though, did have a higher rate of subsequent vitreoretinal surgeries, possibly because of a higher rate of retained subretinal PFCL in this cohort [15]. Moving to preoperative characteristics, the PRO authors reported in the largest series to date on the outcomes of octogenarians or nonagenarians undergoing primary RRD repair.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…A large multicenter retrospective study involving 919 eyes demonstrated that postoperative outcomes were comparable between the two procedures, with a slightly greater number of subsequent procedures needed in the PFCL cohort. 32 Another small RCT with 52 eyes revealed similar final BCVA and OCT parameters, including foveal contour, retinal layers, central macular thickness, and ERM formation. However, postoperative metamorphopsia was less common in the PFCL group.…”
Section: Evidence-based Rationalementioning
confidence: 89%
“…Vo et al also reported on whether PFCL use affected the postoperative results in 159 cases of PFCL using a large database. They also found no significant differences in the final BCVA, re-attachment rates, anatomic success, presence of postoperative epiretinal membrane, and macular pathologies [15]. All of these reports showed that the re-attachment rates with PFCL were good but not significantly better than the non-use of PFCL and showed its advantages for RRD operations.…”
Section: Discussionmentioning
confidence: 99%